Comprehensive Physiology 2011
DOI: 10.1002/cphy.c100010
|View full text |Cite
|
Sign up to set email alerts
|

Gas Exchange Consequences of Left Heart Failure

Abstract: This review explores the pathophysiology of gas exchange abnormalities arising consequent to either acute or chronic elevation of pulmonary venous pressures. The initial experimental studies of acute pulmonary edema outlined the sequence of events from lymphatic congestion with edema fluid to frank alveolar flooding and its resultant hypoxemia. Clinical studies of acute heart failure (HF) suggested that hypoxemia was associated only with the final stage of alveolar flooding. However, in patients with chronic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 101 publications
0
16
0
Order By: Relevance
“…As the solubility of CO 2 remains unchanged, the exercise associated V′A/Q′ shift leads to an increased physiological dead space measurement for CO 2 . Hence a consistent explanation for the elevated dead space measurements seen during exercise in the most impaired heart failure patients is the abnormally elevated overall V′A/Q′ ratio and its interaction with V′A/Q′ heterogeneity [49,50].…”
Section: Abnormal Exercise Dead Space Measurements In Heart Failurementioning
confidence: 90%
“…As the solubility of CO 2 remains unchanged, the exercise associated V′A/Q′ shift leads to an increased physiological dead space measurement for CO 2 . Hence a consistent explanation for the elevated dead space measurements seen during exercise in the most impaired heart failure patients is the abnormally elevated overall V′A/Q′ ratio and its interaction with V′A/Q′ heterogeneity [49,50].…”
Section: Abnormal Exercise Dead Space Measurements In Heart Failurementioning
confidence: 90%
“…Previous work investigating pulmonary gas exchange at rest in subjects with stable left heart failure has found that blood gases and data obtained from studies using the multiple inert gas elimination technique are typically within the normal range expected (Robertson, 2011). Additionally, these studies suggest that the primary cause for any abnormalities in pulmonary gas exchange efficiency is diffusion limitation caused by pulmonary oedema.…”
Section: Patent Foramen Ovale and Arterial Hypoxaemiamentioning
confidence: 76%
“…As a group, subjects with CHF typically have normal arterial oxygenation at rest and even during exercise (Clark & Coats, 1994;Robertson, 2011). Nevertheless, when present, the worsening of pulmonary gas exchange efficiency and arterial hypoxaemia observed in some subjects with CHF is typically attributed to diffusion limitation and pulmonary oedema (Robertson, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations